KEDUDUKAN DAN HAK ANAK TIRI TERHADAP HARTA PENINGGALAN ORANG TUA TIRINYA DITINJAU DARI HUKUM KEWARISAN ISLAM - Muhammad Rizal; Muh. Jufri Ahmad (Gapenas Publisher, 2023)
The existence of stepchildren in a marriage requires legal certainty regarding their rights to the inheritance of their adoptive parents, because after all the presence of stepchildren is deliberately included in a legal marriage and stepchildren are in entitled protection to ensure they are future, regardless of status or status. position. Inheritance in Islamic law is an obligation must be fulfilled and is sometimes highly emphasized because the division of inheritance often causes adverse consequences for a family whose heirs are all left to die. The desire of humans who are too fond of property, often justifies various ways to obtain these assets, including inheritance from their own heirs. Basically, people who have blood relations or blood relations with the heirs become heirs, because of marriage to the heirs (husband or wife of the heir). Based on the above, the author can formulate several related issues, namely what is the position and rights of adopted children over the assets left by adoptive parents? and what about legal certainty regarding the rights of adopted children in the distribution of inheritance or gifts from adoptive parents? The purpose of this research is to find out and describe the position of stepchildren in Islamic inheritance law, then to find out and describe the legal certainty of the rights of stepchildren in the distribution of inheritance or grants given by their adoptive parents. The method used is regulatory research, which is an approach by studying and analyzing existing laws and regulations. The conclusion of this article is that adopted children are not heirs in the family